2015
DOI: 10.3389/fnhum.2015.00673
|View full text |Cite
|
Sign up to set email alerts
|

Theta and Alpha Band Modulations Reflect Error-Related Adjustments in the Auditory Condensation Task

Abstract: Error commission leads to adaptive adjustments in a number of brain networks that subserve goal-directed behavior, resulting in either enhanced stimulus processing or increased motor threshold depending on the nature of errors committed. Here, we studied these adjustments by analyzing post-error modulations of alpha and theta band activity in the auditory version of the two-choice condensation task, which is highly demanding for sustained attention while involves no inhibition of prepotent responses. Errors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 57 publications
8
16
1
3
Order By: Relevance
“…In previous studies, theta increases accompanied alpha suppression and correlated with behavioral measures of post-error adaptation (e.g. Novikov et al 2015). In our study, alpha suppression only occurred later and in combination with the reported post-response beta suppression.…”
Section: Summary Of Findingssupporting
confidence: 84%
“…In previous studies, theta increases accompanied alpha suppression and correlated with behavioral measures of post-error adaptation (e.g. Novikov et al 2015). In our study, alpha suppression only occurred later and in combination with the reported post-response beta suppression.…”
Section: Summary Of Findingssupporting
confidence: 84%
“…Recently, the suppression of alpha activity was connected to sensory attention [ 36 , 37 ]. It was also shown that changes in attention induced by special auditory stimuli can modulate alpha energy [ 38 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Испытуемые выполняли модифицированную слуховую конденсационную задачу, представляющую собой новую перспективную экспериментальную модель для психологических исследований в парадигме когнитивного контроля (Novikov et al, 2015a(Novikov et al, , 2015bЛазарев и др., 2014 Управление экспериментом, предъявление стимулов и регистрацию поведенческих ответов производили с помощью программы «E-Prime» (Psychology Software Tools Inc., США).…”
Section: Appendixunclassified
“…Поведенческие показатели вы полнения задачи в целом соответствуют результатам, полученным ранее при применении сходной слуховой конденсационной задачи с другими стимулами (Novikov et al, 2015a(Novikov et al, , 2015bЛазарев и др., 2014).…”
Section: Appendixunclassified